Slab narrowing in the Central Mediterranean: the Calabro-Ionian subduction zone as imaged by high resolution seismic tomography - L. Scarfì (Nature Portfolio, 2018)
Abstract A detailed 3D image of the Calabro-Ionian subduction system in the central Mediterranean was obtained by means of a seismic tomography, exploiting a large dataset of local earthquakes and computing algorithms able to build a dense grid of measure nodes. Results show that the slab is continuous below the southern sector of the Calabro-Peloritan Arc, but the deformation processes developing at its edges are leading to its progressive narrowing, influencing tectonics and magmatism at the surface, and with possible stress concentration in the tip zones. In the southwest, the deformation occurring at a free slab edge lead to propagation of a vertical lithospheric tear in the overriding plate, which extends along a NW-SE fault system (Aeolian-Tindari-Letojanni) up to about 30 km into the Ionian Sea; further southeast, the lithosphere appears only flexed and not broken yet. In the northeast, the slab seems to break progressively, parallel to the trench. Finally, northwest of Mt. Etna, the tomography highlights low VP that can be related to an upwelling of deep mantle material likely flowing laterally through a window opened by the complete slab detachment.